3D morphometry of De Geer Moraines and Crevasse-Squeeze Ridges: Differentiating between pushing and squeezing mechanisms from remotely sensed data - Rivers Gwyneth E.; Storrar Robert D.; Jones Andrew H.; Ojala Antti E.K. (Elsevier Ltd, 2025)
De Geer Moraines (DGM) and Crevasse-Squeeze Ridges (CSR) are important landforms that can provide useful insights regarding palaeo-glacial processes. Specifically, these landforms can provide information concerning icemarginal dynamics, and/or subglacial processes, depending on the context in which they are formed. The extraction of 3D morphometric data from these ridges can help to elucidate their formational processes, and potentially enable landform differentiation. We develop a new Python-based ArcGIS toolbox that can automatically extract 3D morphometric data from large sample sets of linear features. The morphometry toolbox may be applied to a wide range of research disciplines that are concerned with quantifying the morphometry of any elongated landforms. This is particularly useful for DGM and CSR studies, where visual similarities can result in confusion over landform type and/or formation. Here we present a case study from southwest Finland and the Northwest Territories, Canada, whereby high-resolution 3D morphometric data is used to analyse and classify DGMs and CSRs. The results reveal key differences in morphometric properties between the landforms which enables a quantified foundation by which to differentiate them. The studied CSRs are found to be higher, wider, steeper, more symmetrical, less sinuous and more voluminous than the studied prominent DGM. In contrast, a tendency for cross-sectional asymmetry in DGM supports an origin by ice-marginal pushing, rather than basal squeeze-up into crevasses. This is further supported by CSRs being less sinuous than DGM due to them being constrained to the dimensions and planform of the (relatively straight) host crevasses, whereas DGM follow a more sinuous path related to the ice margin shape. Future work should include sedimentological and geophysical studies to constrain DGM internal architecture and formation processes. The results may then be used to validate the application of DGM for detailed ice marginal reconstructions.